Hairy cell leukemia: current therapies and future directions. Issue 6 (December 2010) - Vosganian, Gregory S; Sigal, Darren S; Saven, Alan
Evaluation of: Zinzani PL, Pellegrini C, Stefoni V et al. Hairy cell leukemia: evaluation of the long-term outcome in 121 patients. Cancer 116(20), 4788–4792 (2010). Hairy cell leukemia is a rare disease for which there are multiple treatment options. Purine nucleoside analogs (cladribine and pentostatin) are generally used for front-line treatment. Other active agents include interferon, rituximab and, although rarely, splenectomy. In the series published by Zinzani et al. in Cancer, the authors conclude that initial treatment for hairy cell leukemia should be maximized since these patients generally enjoy the highest complete response rates and the longest remission durations, and subsequent lines of therapy have lower response rates and more frequent relapses. However, evolving immunohistochemical and molecular diagnostic techniques, as well as criteria for evaluating response to therapy and clinical trials investigating chemoimmunotherapy, may result in clinicians re-evaluating how patients are treated in the front-line and when treatment should be initiated for relapsed patients.